SIBLING STATUS AND BEHAVIOR OF ADOLESCENTS IN CONFLICT SITUATIONS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article is devoted to the scientific substantiation and study of the influence of a teenager's sibling status on interpersonal relationships with peers. The article also describes the peculiarity of the behavior of adolescents from different sibling positions in a conflict situation.